Screening for forms of problematic Internet usage. (April 2023) - Matsuzaki, Takanobu; Nishimura, Kotaro; Higuchi, Susumu
Abstract : This review deals with the screening of four types of addiction related to Internet use: gaming disorder (GD), Internet, smartphone, and social networking addiction. The majority of screening instruments for GD were developed based on the diagnostic criteria included in fifth edition of the Diagnostic and Statistical Manual of Mental Disorders and International Classification of Diseases 11th Revision, but no single tool was clearly superior. Although screening tools have been developed for other types of addiction, globally approved diagnostic criteria for those addictions on which screening tools could be applied and validated have yet to be developed. Further research is warranted to develop an internationally standardized screening tool for GD and to provide sufficient evidence to establish the disease concepts for the remaining addictions. Highlights: Screening tools for DSM-5 and ICD-11 gaming disorder have been developed. No single tool for gaming disorder is superior regarding psychometric properties. Screening tools for other types of Internet-related addiction also exist. Research is necessary to develop a standardized screening tool for gaming disorder. Establishment of disease concepts of other types of addiction is required.